Perlindungan Hukum Terhadap Investor Dalam Investasi Ilegal Akibat Promosi Media Online Influencer Melalui Akun Youtube - Shelsy Merinda; Dian Amelia; Upita Anggunsuri (Fakultas Hukum Universitas Andalas, 2023)
The use of social media in online investment activities should ideally provide convenience to the public for investing their assets. The prevalence of online investments within the community does not rule out the possibility that some of them are illegal or unauthorized investments, leading to losses for citizen. Legal protection can be provided to investors namely domains of illegal futures brokerage companies, cessation of illegal futures trading promotion, monitoring and observation of illegal futures trading sites by the regulatory authority. However, there are no explicit rules regarding penalties for influencers promoting binary option trading due to the lack of clear regulations about binary options. The research questions addressed in this study are: What is legal protection to investors in illegal investments YouTube? What is the function of BAPPEBT) to prevent illegal investments due to online influencer promotions YouTube? This research uses the normative juridical. The Conclusion of the research are BAPPEBTI offers preventive protection to the public by continually monitoring and educating about investment procedures in line with regulations. BAPPEBTI can block illegal sites based on regulation, but it can’t prohibit binary option trading due to the persistent emergence of domain sites. Contradictory regulations regarding the submission of claims for Restitution and Compensation result in investors lacking legal protection. BAPPEBTI’s role involves ongoing efforts in monitoring, observation, blocking illegal investment websites, education, and public awareness campaigns. BAPPEBTI is also part of the anti investment scam task force to halt investment solicitation and remove content related to Quotex and binary options.